Učenje in poučevanje v visokem šolstvu: Spoznanja in izzivi (University of Maribor Press, 2021)
Learning and Teaching in Higher Education: Lessons and Challenges. At the higher education level, researchers and developers of contemporary practices increasingly focus on student-centred learning and teaching. Students are thus placed in the role of active participants in the educational process that can help shape the educational process and take full responsibility for their performance and the path they choose. University teachers and their competencies have a key role in this process, as they must design innovative learning environments so that students are encouraged and empowered to make responsible choices about their educational process. The scientific monograph Learning and Teaching in Higher Education: Findings and Challenges contains various contemporary views on this topic, from both a pedagogical and didactic perspective and a psychological one. The monograph consists of an editorial that introduces the chapters’ content and links the chapters together and eight chapters with different but essentially related contents that are meaningfully complemented and enhanced.